Desenvolvimento e avaliação da viabilidade de implantes intraoculares constituídos de poliuretano biodegradável e bevacizumabe - Elionai Cassiana de Lima Gomes (2011)
The treatment of diseases of the posterior segment of the eye is limited by the difficulty in delivering effective doses of the drug to the vitreous, retina and choroid. Intravitrea l injections have been used to deliver drugs to the posterior segment of the eye, but it is an invasive technique and shows risk of infections and damages in ocular tissues. Aiming to reach adequate therapeutic range of the drugs in the posterior segment of the eye for long periods, controlled drug release polymeric systems implanted directly in the vitreous have been investigated for the treatment of several ocular diseases. Such systems eliminate the need for repeated applications, since the drug is released over a period of time, thus presenting a huge advantage over injections. In this study, a biodegradable aqueous dispersion of polyurethane was synthesized, and bevacizumab was incorporated to it. From this incorporation, implants made of polyurethane and bevacizumab were developed and evaluated as intraocular devices for controlled drug delivery for the treatment of proliferative diabetic retinopathy and age-related macular degeneration. These implants were characterized by FTIR, XRD and thermal analysis, and also submitted to in vitro drug release study. The drug was quantified by the analytical method previously developed and validated. Different characterization techniques revealed that bevacizumab interacted with polyurethane when dispersed in the polymer matrix. This interaction was further confirmed by in vitro release study, since no peaks concerning to the drug were detected during the study. Therefore, the polyurethane used in this work showed no viability for use in delivery systems for prolonged bevacizumab. Keywords: Polyurethane, bevacizumab, intraocular implants, controlled drug release, posterior segment of the eye